Sidetracked why our decisions get derailed, and how we can stick to the plan - Gino, Francesca (Harvard Business Review Press, 2013)
A psychologist and business professor takes an in-depth look at decision-making, explaining the pitfalls people can avoid to stay on track with their decisions and reach their goals
Includes bibliographical references and index
Introduction: what gets us off track? -- Forces from within -- Better than Mother Theresa: inaccurate views of ourselves -- The unreliable motorcycle racer: infectious emotions -- What the cracked pot couldn't see: an overly narrow focus -- Forces from our relationships -- How to draw an e on your forehead: lack of perspective taking -- The curse of the blue t-shirt: insidious social bonds -- The power of stickers: salient social comparisons -- Forces from the outside -- They're not as dumb as you think they are: irrelevant information -- Traveling to Europe on pudding: subtle changes in framing -- Cheaters in sunglasses : ambiance and opportunity -- Conclusion: sticking to the plan
Keywords: Decision making; Decision Making; Entscheidungsfindung; Entscheidung; Entscheidung bei Unsicherheit; Risiko